Prediction of high salt and low potassium intake behavior from urinary sodium and potassium excretion in Japan - Horikawa, Chika; Murayama, Nobuko; Sasaya, Mizue; Sakai, Maiko; Sano, Michiko; Takizawa, Norihiko; Takano, Mayumi (Progress in Nutrition, 2019)
Salt reduction policies have been implemented worldwide and increased potassium intake is also recommended. However, simultaneous investigations of dietary behavior and sodium and/or potassium intake estimated by urinary excretion are sparse. This study aimed to predict high salt and low potassium intake based on dietary behaviors in Japan. The study was comprised of 2627 participants aged 20 to 74 years (Men%: 50%) living in Niigata City, Japan. Participants completed a questionnaire about dietary behaviors potentially relevant to salt and potassium intake. A casual urine specimen for estimating dietary salt and potassium intake per day was collected the same day. The relationship of estimated dietary salt and potassium intake to questionnaire responses was examined using analysis of covariance for age, gender, and body mass index. Twenty-eight items on the questionnaire revealed an association with dietary salt and/or potassium intake and were divided into 4 categories: related to both high salt and low potassium intake, only high salt intake, only low potassium intake, and both high potassium and high salt intake. Identified were 28 dietary behaviors that enabled the prediction of high salt and low potassium intake behavior and provided information for encouraging decreased salt intake and increased potassium intake among Japanese.